ANTIBIOTICS FOR APPENDICECTOMY IN CHILDREN AND ADOLESCENTS DURING THE PERIOPERATIVE PERIOD: AN INTEGRATIVE REVIEW - Fátima Maria Castelo Branco Roque; Antônio Aldo Melo Filho; Alberto Jorge Castelo Branco Roque; Hanne Castelo Branco Roque; Thereza Maria Magalhães Moreira; Edna Maria Camelo Chaves
ABSTRACT Objective: To analyze the preoperative use of antibiotics in children and adolescents requiring appendectomy. Data source: Integrative review was performed in the MEDLINE, Latin American and Caribbean Health Sciences (LILACS) and Cochrane databases and the PubMed portal, with no time limit. The keywords used were: appendicitis, child, adolescent and antibacterial with Boolean AND. The articles included were published in Portuguese, English or Spanish and whose participants were under 18 years of age. Review articles and guidelines were excluded. The studies were classified according to their level of evidence and 24 papers were selected. Data collection and analysis: Seven randomized clinical trial studies (level of evidence II), eight cohorts (level III), seven retrospective observational studies (level V) and two historical documentary analysis (level IV) were selected. The studies addressed antibiotics used in acute appendicitis in both uncomplicated and complicated cases. Antibiotics initiated in the preoperative period showed a decrease in the rates of surgical wound infections. First-line (empiric) regimens were tested for sensitivity to microorganisms in peritoneal material cultures, however the results were controversial. Broad-spectrum antibiotics have been suggested in some studies because they have good coverage, but in others they have not been recommended because of the risk of developing bacterial resistance. Shorter administration time and earlier change to the oral route reduced hospitalization time. Conclusions: There are several clinical protocols with different antibiotics. However, there is no standardization concerning the type of antibiotic drug, time of use, or route.